Biological prospecting in Antarctica : is there a need for intensive cooperation between the BBNJ and the ATCM over bioprospecting in ABNJ? - Heinrich, Katharina, 1992- (2019)
The ocean, of which 64% is constituted of areas beyond national jurisdiction (ABNJ), among these also the Polar Regions, is rich in biological diversity. Marine organisms within these areas have adapted to these extreme environments but due to the increase of human activities marine biodiversity is threatened. By establishing the Convention on Biological Diversity (CBD), which also includes bioprospecting activities, biodiversity’s conservation and sustainable use shall be ensured. However, ABNJ are left widely unregulated and bioprospecting activities lack specific regulation. Also in Antarctica bioprospecting has raised concerns and the matter has been discussed since 2002. In light of this situation the United Nations General Assembly Resolution UNGA 69/292 has decided the establishment of a new international legally binding instrument (ILBI) on the conservation and sustainable use of marine biological diversity. Yet, the inclusion of the Antarctic Treaty area remains unclear. As the ATCM only acknowledges the Antarctic Treaty System as the appropriate framework to regulate these activities in Antarctica, the thesis investigates whether there is a need for extensive research between those two entities – the UN Biodiversity Beyond National Jurisdiction (BBNJ) working group and the A TCM – over bioprospecting activities in ABNJ. Based on a comprehensive literature review on bioprospecting activities within ABNJ and Antarctica as well as a review of the current legal framework, a scenario on cooperation between the ATCM and the BBNJ working group is established. The thesis concludes by stating that even though there might not be a reference to Antarctic marine genetic resources in the new ILBI, the BBNJ and the ATCM should establish cooperation on regulating these activities as they are facing the same issues and need to ensure a consistent set of frameworks regulating the conservation of biodiversity in ABNJ.